Attributes of the Cultural Landscape. Reflections on Cultural Landscape, as a typology and Historic Urban Landscape, as an approach. - Silva, Paula Maciel; Câmara, Andrea; Duarte, Clarissa (Technical and Scientific Journal Green Cities, 2025)
The aim of the work is to identify the attributes of the cultural landscape that carry the value to be preserved. It begins with a theoretical approach to the theme of cultural landscape using Content Analysis as a text analysis methodology. The results indicate that a large part of the values is related to the spatial organization and form, the material genuineness and the continuity of the scenario, all of these aspects related to the urban form. In the second part, it is proposed to read the landscape to integrate the perspectives generated by the viewpoints. It is an alternative approach to defining a uniform radius of coverage for defining the protection zone. The focus is on the scale of the building complex as one of the elements that can negatively impact the landscape. This is a methodological approach to the research. The aim is to contribute to the reading of the territory and offer subsidies for the development of urban rehabilitation guidelines that include the preservation, restoration and revitalization of the landscape.
Keywords: Heritage; Cultural landscape; Sustainable buildings